2003
DOI: 10.1002/cii.79
|View full text |Cite
|
Sign up to set email alerts
|

Performance and benefit as outcome measures following cochlear implantation in non-traditional adult candidates: a pilot study

Abstract: Objectives To measure the reported benefit in quality of life (QoL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…A more robust way of assessing patient-reported benefits is to use validated quality of life tools for assessing benefit. A mean Glasgow Benefit Inventory score of 38.9 after CI was reported by one group, comparable to the mean score of 40 reported for "traditional" CI recipients [Peasgood et al, 2003]. Straatman et al [2014] also reported improvement in both disease-specific and generic quality of life questionnaire scores in a group of 28 patients, all of whom had some auditory input in the past and used primarily auraloral communication.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…A more robust way of assessing patient-reported benefits is to use validated quality of life tools for assessing benefit. A mean Glasgow Benefit Inventory score of 38.9 after CI was reported by one group, comparable to the mean score of 40 reported for "traditional" CI recipients [Peasgood et al, 2003]. Straatman et al [2014] also reported improvement in both disease-specific and generic quality of life questionnaire scores in a group of 28 patients, all of whom had some auditory input in the past and used primarily auraloral communication.…”
Section: Discussionsupporting
confidence: 53%
“…Most NT recipients use their cochlear implant regularly [Zwolan et al, 1996]. The literature indicates high satisfaction ratings similar to those of conventional CI candidates; mean satisfaction ratings of between 83 and 97% have been reported [Peasgood et al, 2003;Chee et al, 2004]. A more robust way of assessing patient-reported benefits is to use validated quality of life tools for assessing benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they were often considered poor cochlear implant (CI) candidates. At the same time, studies reported that, in spite of these poor outcomes, satisfaction rates were high [Hinderink et al, 1995;Kaplan et al, 2003;Peasgood et al, 2003;Zwolan et al, 1996]. As speechcoding strategies evolved towards SPEAK, CIS and ACE from the late 90s onwards, studies showed that more beneficial results were possible for prelingually deafened adults [Schramm et al, 2002;Waltzman and Cohen, 1999;Waltzman et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Peasgood and colleagues 50 found no speech recognition in adults with late cochlear implants, and much less favorable results than are associated with cochlear implants in general.…”
Section: Duration Of Preimplant Deafnessmentioning
confidence: 97%